2018
DOI: 10.1557/mrc.2018.186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of angular deviation from coincidence site lattice grain boundaries on hydrogen segregation and diffusion in α-iron

Abstract: Coincidence Site Lattice (CSL) grain boundaries (GBs) are believed to be low-energy, resistant to intergranular fracture, as well as to hydrogen embrittlement. Nevertheless, the behavior of CSL-GBs are generally confused with their angular deviations. In the current study, the effect of angular deviation from the perfect Σ3 (111) [110] GBs in α-iron on the hydrogen diffusion and the susceptibility of the GB to hydrogen embrittlement is investigated through molecular static and dynamics simulations. By utilizin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The results of the mean GB segregation energy based on PDF fitting and 95% confidence interval within the 30 Å layer are summarized in figure 2 for the three studied CSL-GBs for different φ. Based on previous studies [25,26]; the ideal 3 (111) GB showed preferable attraction to H atoms, due to the low segregation energy of H to GB, with a mean value of −0.34 eV. Additionally, as shown by Rajagopalan et al [21],…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The results of the mean GB segregation energy based on PDF fitting and 95% confidence interval within the 30 Å layer are summarized in figure 2 for the three studied CSL-GBs for different φ. Based on previous studies [25,26]; the ideal 3 (111) GB showed preferable attraction to H atoms, due to the low segregation energy of H to GB, with a mean value of −0.34 eV. Additionally, as shown by Rajagopalan et al [21],…”
Section: Resultsmentioning
confidence: 87%
“…Figure 3 shows the H and C free-surface segregation energy, for the studied CSL-GBs and their deviations. 3 (111) GB results are shown in figure 3(a), there are no significant differences between H free-surface segregation energy values with varying φ except for φ = 5 • ; where the H freesurface segregation energy is the maximum with mean value of −0.43 eV [25,26] and thus showing a lower tendency for H to segregate to this deviated surface. By extending the previous H segregation to free-surface study to C segregation, it can be shown that the lowest C segregation energy to free-surface is at the ideal free-surface orientation with mean value of −0.35 eV.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The excess volumes of GBs were progressively measured at different atomic hydrogen The previous study suggested that excess volume was closely related to the stability of a GB [29]. After hydrogen atoms were randomly inserted into the tetrahedral sites [30,31] within a rectangular zone (which was 10 Å away from the GBs), the system was relaxed for 2 ns to allow hydrogen atoms to segregate into the grain boundary region. As all the hydrogen atoms initially placed near GBs would segregate into the GBs, the concentration of hydrogen atoms in the same set of tests was consistent.…”
Section: Hydrogen Effects On Gb Energy and Excess Volumementioning
confidence: 99%
“…In the preliminary simulation results, the material was compressed along the Y-axis and the lower edge was constrained. This work follows Hatem and Zikrymodels as presented [23][24][25][26][27][28] . Therefore, the Crystal plasticity (CP) phenomenologicalbased modelling along with specialized Fourier spectral solvers; that utilize fast Fourier transform (FFT), are used to study the material behaviour as well as the failure in the material.…”
Section: B-microscale Modellingmentioning
confidence: 99%